(untitled) (Sebha University Conference Proceedings, 2025)
For optimal photovoltaic (PV) power-generation conversion, maximum power point tracking (MPPT) is essential. This study introduces a reliable and advanced third-order sliding mode control (TOSMC) based MPPT, aimed at addressing its main drawbacks such as chattering phenomena and voltage and power ripples. In order to demonstrate the capabilities of the proposed TOSMC control, a comprehensive study has been conducted. This study compares the TOSMC control with traditional perturb & observe and incremental conductance methods. Various factors such as tracking time, power oscillations, voltage and current ripples, robustness, and power efficiency have been taken into consideration. The verification of the recommended PV system is conducted using the MATLAB interface. Hence, diverse scenarios of atmospheric conditions have been applied such as fast fluctuation and realistic changing of irradiation across one day. The results obtained provide strong evidence for the effectiveness of the control method utilized, demonstrating superior performance.